A study on outcome of standardized treatment in multi-drug resistance tuberculosis patients - N., Neeta P.; N., Prashanth; Ramaprasad, G.; Goud, T. Gangadhar; B., Sameena A.R. (International Journal Of Community Medicine And Public Health, 2017)
Background: Programmatic management of Multi-drug resistance Tuberculosis (MDR-TB) using a standardized treatment regimen (STR) is being implemented under the Revised National Tuberculosis Control Programme (RNTCP) in India. Our study was undertaken to analyze the outcomes of MDR-TB patients treated at the Drug resistance centre (also known as Dots Plus Centre, DR-TB) Bellary, with the RNTCP recommended 24-27months STR, under programmatic conditions. Methods:Patients confirmed to have MDR-TB by Line Probe Assay (LPA) method, from Intermediate reference laboratory (IRL) Bangalore, were treated with the RNTCP’s STR in a prospective field trial on a predominantly ambulatory basis. Forty three patients were enrolled to the trial from December 2012 to April 2013. Results: At the end of treatment, 19 (44.2%) were cured, 12 defaulted, 9 died, 1 failure and 2 were under XDR TB evaluation. Thirty two (74.2%) patients reported adverse drug reactions (ADRs) which required dose reduction or termination of the offending drug. No patient had XDR-TB initially, but 3 cases emerged for XDR-TB evaluation during treatment. Before start of treatment mean body mass index (BMI) was 17.67±3.627 kg/mt2. 34 patients had far advanced lesions on chest x-ray. Outcome was better in those patients, whose tubercular bacilli resistant both to rifampicin and isoniazid and who had good adherence in the past tubercular treatment. Conclusions:Outcomes of this small group of MDR-TB patients treated with the RNTCP’s STR is encouraging in this setting. Close attention needs to be paid to ensure adherence, and to the timely recognition and treatment of ADRs.